Association of plasminogen activator inhibitor-1 and low-density lipoprotein heterogeneity as a risk factor of atherosclerotic cardiovascular disease with triglyceride metabolic disorder: a pilot cross-sectional study. Issue 7 (November 2017) - Iida, Kiyoshi; Tani, Shigemasa; Atsumi, Wataru; Yagi, Tsukasa; Kawauchi, Kenji; Matsumoto, Naoya; Hirayama, Atsushi
Abstract : Background: We hypothesized that an increase in plasminogen activator inhibitor 1 (PAI-1) might reduce low-density lipoprotein (LDL) particle size in conjunction with triglyceride (TG) metabolism disorder, resulting in an increased risk of atherosclerotic cardiovascular disease (ASCVD). Methods: This study was carried out as a hospital-based cross-sectional study in 537 consecutive outpatients (mean age: 64 years; men: 71%) with one or more risk factors for ASCVD from April 2014 to October 2014 at the Cardiovascular Center of Nihon University Surugadai Hospital. The estimated LDL-particle size was measured as relative LDL migration using polyacrylamide gel electrophoresis with the LipoPhor system. The plasma PAI-1 level, including the tissue PA/PAI-1 complex and the active and latent forms of PAI-1, was determined using a latex photometric immunoassay method. Results: A multivariate regression analysis after adjustments for ASCVD risk factors showed that an elevated PAI-1 level was an independent predictor of smaller-sized LDL-particle in both the overall patients population ( β =0.209, P <0.0001) and a subset of patients with a serum low-density lipoprotein cholesterol (LDL-C) level lower than 100 mg/dl ( β =0.276, P <0.0001). Furthermore, an increased BMI and TG-rich lipoprotein related markers [TG, remnant-like particle cholesterol, apolipoprotein (apo) B, apo C-II, and apo C-III] were found to be independent variables associated with an increased PAI-1 level in multivariate regression models. A statistical analysis of data from nondiabetic patients with well-controlled serum LDL-C levels yielded similar findings. Furthermore, in the 310 patients followed up for at least 6 months, a multiple-logistic regression analysis after adjustments for ASCVD risk factors identified the percent changes of the plasma PAI-1 level in the third tertile compared with those in the first tertile as being independently predictive of decreased LDL-particle size [odds ratio (95% confidence interval): 2.11 (1.12/3.40), P =0.02]. Conclusion: The plasma PAI-1 levels may be determined by the degree of obesity and TG metabolic disorders. These factors were also shown to be correlated with a decreased LDL-particle size, increasing the risk of ASCVD, even in nondiabetic patients with well-controlled serum LDL-C levels.